Topical corticosteroid addiction and phobia - Aparajita Ghosh; Sujata Sengupta; Arijit Coondoo; Amlan Kusum Jana (Indian Journal of Dermatology, 2014)
Corticosteroids, one of the most widely prescribed topical drugs, have been used for about six decades till date. However, rampant misuse and abuse down the years has given the drug a bad name. Topical steroid abuse may lead to two major problems which lie at the opposing ends of the psychosomatic spectrum. Topical steroid addiction, a phenomenon that came to be recognized about a decade after the introduction of the molecule is manifested as psychological distress and rebound phenomenon on stoppage of the drug. The rebound phenomenon, which can affect various parts of the body particularly the face and the genitalia has been reported by various names in the literature. TC phobia which lies at the opposite end of the psychiatric spectrum of steroid abuse has been reported particularly among parents of atopic children. Management of both conditions is difficult and frustrating. Psychological counseling and support can be of immense help in both the conditions.